Work Professionalism toward Improving Administrative Governance of the Jauh Pandang Village Government, Pitumpanua District, Wajo Regency - Mutahhara Taufik; Andi Uceng; Erfina (MultiTech Publisher, 2024)
Determining the level of professionalism in the job and enhancing the administrative governance of the Jauh Pandang Village, Pitumpanua District, Wajo Regency government are the goals of this study. Random sampling was the sampling method employed. In this study, 91 individuals made up the sample, out of a total population of 1.080. The results of this research show that the professionalism of the apparatus is 75% in the good category. Improved administrative governance 68% good category. This shows that work professionalism has an impact on improving administrative governance in Jauh Pandang Village, Pitumpanua District, Wajo Regency with a value of t-table < t-count (2.515 > 1.666) with a percentage of 71%, where work professionalism affects improving administrative governance